Timeout for Contrast: Using Physician Behavior Modification to Reduce Contrast in the Catheterization Laboratory - Robby Singh; Marcel Zughaib (Cardiology Research and Practice)
Background. As the number of procedures using contrast media continues to rise, the ensuing complications place an ever increasing burden on the healthcare system. Contrast-induced nephropathy (CIN) is a common postprocedural complication after cardiac catheterization. Objectives. The purpose of our study was to evaluate the impact of physician behavioral modification on reducing the amount of contrast used during the procedure. Methods. All patients who underwent procedures in the cardiac catheterization laboratory from January 2013 to August 2016 were identified in addition to the total contrast used during the procedure, the type of procedure performed, and the operator performing the procedure. A new addition was made to the preprocedure checklist in September-October 2013 in the form of maximum allowed contrast for the patient. Results. A total of 12,118 cases were identified. Across all procedures, the mean contrast used during the 8 months prior to the intervention was 118 ml per procedure. Mean contrast used per procedure for the first year after the revised timeout was 105 ml, for the second year was 106 ml, and for the third year was 99 ml. Conclusion. A significant reduction in radiocontrast use across all operators and procedures after the introduction of a revised timeout procedure that was seen, which is a change that was sustained over a period of three years. With this straightforward intervention involving physician behavioral modification, patients were exposed to less of the nephrotoxic contrast and were consequently at a lower risk of developing dose-depended CIN and other associated complications.